RAB42 Promotes Glioma Pathogenesis via the VEGF Signaling Pathway - Liu, Baoling; Su, Quanping; Xiao, Bolian; Zheng, Guodong; Zhang, Lizhong; Yin, Jiawei; Wang, Lijuan; Che, Fengyuan; Heng, Xueyuan (Frontiers in Oncology, 2021)
Angiogenesis plays an important role in tumor initiation and progression of glioma. Seeking for biomarkers associated with angiogenesis is important in enhancing our understanding of glioma biologically and identifying its new drug targets. RNA-sequencing (RNA-seq) data and matched clinical data were downloaded from the CGGA database. A series of filtering analyses were performed to screen for reliable genes: survival, Multivariate Cox, ROC curve filtration, and clinical correlation analyses. After immunohistochemical verification, RAB42 was identified as a reliable gene for further Single Gene analysis. Afterwards, we performed gene set enrichment analysis (GSEA) and Co-expression analysis to establish the related molecular mechanisms and signal pathways in glioma. Finally, the gene functions and the mechanisms were investigated in vitro experiments.A total of 23270 mRNA expression and 1018 glioma samples were included in this study. After the three filtering analyses, we selected ten genes for immunohistochemical verification: KLHDC8A, IKIP, HIST1H2BK, HIST1H2BJ, GNG5, FAM114A1, TMEM71, RAB42, CCDC18, and GAS2L3. Immunostaining demonstrated that RAB42 was significantly expressed on the membrane of glioma tissues but not in normal tissues. These results were verified and validated in GEPIA datasets, and the association between RAB42 with clinical features was also evaluated. Analysis of gene function indicated that RAB42 activated VEGF signaling pathways and was associated with natural killer cell mediated cytotoxicity, JAK-STAT signaling pathway and apoptosis pathways by PI3K/AKT in gliomas. Experiments in vitro suggested that the proliferation and invasion of glioma cells might be inhibited after downregluating of RAB42. And the tumorigenesis promotion of RAB42 may relate to the activation of VEGF signaling pathway.Taken together, this study shows that the overexpression of RAB42 is an independent prognostic factor of adverse prognosis. Its pro-oncogenic mechanism may be associated with the activation of VEGF signaling pathways.